Reflections on the relationships between research, power and representation - Sepúlveda Chávez, Miguel (2021)
The purpose of this work is to reflect on the praxis and work of social research, mainly the one understood as committed or militant. Thus, it seeks firstly to make visible the authority that researchers have. Secondly, the limits and limitations of the subordinate category will be explored, using it as an example of the categories and nominations used within said kind of research. Finally, an attempt on accounting the challenges surrounding the practice of committed research will be made.